Adopting Currency Convertibility : Experiences and Monetary Policy Considerations for Advanced Developing Countries - Quirk, Peter (IMF Working Papers; Working Paper ;, 1994)
This paper analyses issues for developing countries with structurally sound balance of payments that are considering a move to full currency convertibility. The main experiences of industrial countries in their decontrol of international capital transactions are reviewed, with an emphasis on the implications for monetary policy. The paper deals both with stabilization, and the prudential issues, which are especially important in view of the potential for speculative bubbles. Respective roles of the international organizations, IMF, OECD, and the GATT, in assisting the capital liberalization process are discussed.